Spatial Regression Analysis of Environmental and Structural Factors Influencing Shophouse Values in Makassar City, Indonesia - Najang, Abdullah; Gultom, Parapat; Octavianus, Handy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the factors that influence shophouse values in Makassar City, Indonesia, using a spatial regression model. The research addresses the lack of prior studies that consider spatial dependencies in property value assessments. By analysing data from 101 shophouses across four distinct city strata, factors such as building area, certificate type, and road width were found to significantly impact property values. Additionally, spatial relationships between neighboring properties were observed, indicating a 0.3 positive correlation. The study employed Structural Equation Modeling (SEM) with the R Project for Statistical Computing. The results provide insights into the spatial dynamics of urban property values, which are valuable for urban planners, investors, and policymakers aiming to optimize real estate development in rapidly growing urban centres.